The effect of mind mapping assignment on creative thinking skills and biology concepts mastery in Senior High School - Azizurahmah, Annisyah; Sukarso, AA; Kusmiyati, Kusmiyati; Handayani, Sri (Jurnal Pijar Mipa, 2023)
This study aims to ascertain how grade XI students at SMAN 8 Mataram's mind mapping assignment affects their capacity for original thought and their grasp of biological ideas. On samples chosen by random sampling, this study employed a pretest-posttest control group design and a quasi-experiment. While written assessments in multiple-choice questions were used to get information on topic mastery, mind-mapping assignments were used to gather information on students' creative thinking abilities. The findings demonstrated that mind-mapping exercises significantly impacted students' comprehension of biological topics and enhanced their capacity for creative thought, moving them from less creative to highly creative criteria. Pearson correlation test results showed a positive relationship between creative thinking skills and students' mastery of biological concepts in the medium correlation category. Mind mapping assignment has a positive influence in improving creative thinking skills and mastery of biological concepts of high school students, where students become more creative by simply connecting their prior knowledge with subsequent knowledge.